Development and validation of a HPLC-UV method for the simultaneous detection and quantification of paclitaxel and sulforaphane in lipid based self-microemulsifying formulation. (23rd October 2019) - Kamal, Mohammad M; Nazzal, Sami
Abstract: Paclitaxel (PTX) and sulforaphane (SFN) are known anticancer molecules. Their activity was found to be potentiated when tested concurrently. Only recently, however, a novel SFN enabled PTX self-microemulsifying formulation (SMEDDS) was developed for their simultaneous delivery. This necessitated the development of an analytical method for the simultaneous detection and quantitation of PTX and SFN. In this study, a simple and sensitive isocratic high performance liquid chromatography-ultraviolet (HPLC-UV) analytical method was developed and validated per International Conference on Harmonization guidelines to satisfy this objective. Its application was demonstrated when quantifying the amount of PTX and SFN released from the SMEDDS in various dissolution media. The separation of the analytes was performed with the aid of a reversed phase C18 column at ambient temperature using a 60:40 mixture of acetonitrile and KH2 PO4 buffer (pH 5.0) as the mobile phase. PTX and SFN peaks were detected at 202 nm with high resolution without interference from excipients. This method showed linearity within 2.5–100 μg/mL range with r 2  > 0.999. The limit of detection and lower limit of quantitation were 0.1638 and 0.4964 μg/mL for PTX and 0.4419 and 1.3389 μg/mL for SFN, respectively. A total of 98–101% of the injected samples was recovered with RSD of 0.06–0.68% indicating the suitability of the method for the simultaneous detection and quantitation of the molecules in dissolution media.